TINGKAT PENGETAHUAN REMAJA PUTERI TENTANG ANEMIA GIZI BESI DI SMA DHARMA BHAKTI MEDAN - Lola Pebrianthy; Dewi Agussana; Era Friska (JURNAL KEBIDANAN KESTRA (JKK), 2019)
In the stage of growth and development, adolescence is the stage where a person experiences a transition to adulthood. Nutritional needs in adolescents are higher than the age of the child. Increased nutritional requirements in adolescence were energy, protein, calcium, iron and zinc. Many problems faced by adolescents related to nutrition and health problems. As for the problems that were usually experienced in the teenage phase are Obesity and Anemia. Anemia is a condition when the number of red blood cells or the amount of hemoglobin in red blood cells was below normal. In women, normal hemoglobin is 12-16 gr percent and erythrocytes 3.5-4.5 million / mm3. Many things could be factors anemia, one of the causes was a lack of iron (Fe) so called iron deficiency anemia or iron nutritional anemia. This research was descriptive by using primary data obtained through the use of questionnaires where the sample used was total sampling from the entire population, namely 32 female students of SMA Dharma Bhakti Medan. In this research found the majority of respondents had a sufficient level of knowledge as many as 27 people (84.37%). For this reason, it was expected that the SMA Dharma Bhakti Medan students can expand their knowledge, especially about Iron Nutrition Anemia to find out the signs and symptoms of Iron Nutrition Anemia in order to prevent the occurrence of cases of Iron Nutrition Anemia in young women.